Pengaruh Pendidikan Kesehatan Tentang Pencegahan Penyakit Hiv-Aids Terhadap Pengetahuan Masyarakat di Wilyah Kerja Puskesmas Mabodo - Azim, La Ode Liaumin (Jurnal Ayurveda Medistra, 2026)
HIV-AIDS remains a public health threat in Indonesia, including in rural areas such as Muna Regency. Low public awareness in the Mabodo Community Health Center (Puskesmas) working area is a major obstacle in efforts to prevent and break the chain of stigma. This study aims to determine the effect of health education on HIV-AIDS prevention on public awareness in the Mabodo Community Health Center working area in Muna Regency in 2025. This study used an analytical design with an experimental approach and a one-group pretest-posttest design. The study population consisted of 46 respondents, and the sample also consisted of 46 respondents, which were selected using total sampling technique. The study variables were measured using a questionnaire that had been tested for validity and reliability. The measured data were then processed and analyzed using SPSS version 25.0 and tested using the Wilcoxon test. The statistical test results showed that the respondents' knowledge before receiving health education was 53.69 on average, while their knowledge after receiving health education was 78.04 on average, with a p-value of 0.000. It can be concluded that health education is effective in increasing public knowledge about HIV/AIDS prevention in rural areas. It is recommended that local health centers integrate this education program on a regular basis to improve health literacy and reduce the number of new cases.